A place for the Bodhisatta: The local and the universal in jātaka stories - Appleton, Naomi (Acta Orientalia Vilnensia, 2007)
Oxford University Jātakas—stories about the past lives of the ‘historical’ Buddha—are often associated with specific locations, both within the land of Buddhism’s birth, and in other parts of Asia. There are records suggesting that such locations became early pilgrimage sites; contemporary sources also make reference to ‘local’ jātakas, which in many cases help to assimilate Buddhism into the local culture through its geography. In this article I will argue that it is the structure of jātaka stories that allows this localisation to take place all over Asia. I contend that since the jātakas themselves are lacking in specific external referents they can easily be given a location, whilst their framing in the ‘present’ time of the Buddha’s teaching career grounds the stories in both time and place, without infringing on the flexibility of the individual stories. This ability to provide centrally legitimated relevance for each and all contributes greatly to the popularity and endurance of the jātaka genre. The layering of meanings must remain if the stories are to accomplish this: if the stories become formally localised, for example by 19th century scholars who celebrate the jātakas’ worth as records of life in early India, the power of the stories to transcend boundaries of time and place for their multiple audiences is lost. Yet if the jātakas were not anchored in the Buddha’s teaching career in the 5th century BCE North India, their significance for Buddhists would in any case be negligible.